2014
DOI: 10.1007/s00256-014-1903-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of choline-PET/CT, MRI, SPECT, and bone scintigraphy in the diagnosis of bone metastases in patients with prostate cancer: a meta-analysis

Abstract: Published data on the diagnosis of bone metastases of prostate cancer are conflicting and heterogeneous. We performed a comprehensive meta-analysis to compare the diagnostic performance of choline-PET/CT, MRI, bone SPECT, and bone scintigraphy (BS) in detecting bone metastases in parents with prostate cancer. Pooled sensitivity, specificity, and diagnostic odds ratios (DOR) were calculated both on a per-patient basis and on a per-lesion basis. Summary receiver operating characteristic (SROC) curves were also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
210
2
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(231 citation statements)
references
References 50 publications
3
210
2
16
Order By: Relevance
“…Consensus decision as well as follow-up data support the credibility of the ACE-PET/CT findings. Our results are in line with previous publications, such as the meta-analysis of BS, MRI and 11 C-choline-PET/CT by Shen et al, which concluded that BS was the least specific and least sensitive modality (16). Another study showed better specificity but lower sensitivity for detection of bone metastases from PC with 11 C-choline-PET/CT compared to BS (19).…”
Section: Discussionsupporting
confidence: 82%
“…Consensus decision as well as follow-up data support the credibility of the ACE-PET/CT findings. Our results are in line with previous publications, such as the meta-analysis of BS, MRI and 11 C-choline-PET/CT by Shen et al, which concluded that BS was the least specific and least sensitive modality (16). Another study showed better specificity but lower sensitivity for detection of bone metastases from PC with 11 C-choline-PET/CT compared to BS (19).…”
Section: Discussionsupporting
confidence: 82%
“…This in turn makes recommendations for a specific therapeutic approach of the oligometastatic state even more difficult [41][42][43].…”
Section: Oligometastatic Castration-naïve Prostate Cancermentioning
confidence: 99%
“…A metaanalysis by Shen et al (23) of 27 studies compared the diagnostic performance of 11 C-and 18 F-choline PET/CT, MRI, bone SPECT, and bone scintigraphy for detecting bone metastases in patients with prostate cancer. On a per-patient basis, the pooled sensitivities of 11 C-and 18 F-choline PET/CT, MRI, and bone scintigraphy were 91%, 97%, and 79%, respectively, and the pooled specificities were 99%, 95%, and 82%, respectively.…”
Section: F-fluorocholine Pet/ctmentioning
confidence: 99%